Coronary Stent Healing in Cancer Patients—An Optical Coherence Tomography Perspective - Aziz, Moez Karim; Herrmann, Joerg; Marmagkiolis, Konstantinos; Balanescu, Dinu Valentin; Donisan, Teodora; Pushparaji, Bala; Lin, Heather Y.; Tomakin, Gerryross; Hoyt, Taylor; Pham, Martin; Dijkstra, Jouke; Cilingiroglu, Mehmet; et al. (Frontiers in Cardiovascular Medicine, 2021)
Objective: This study assessed stent healing patterns and cardiovascular outcomes by optical coherence tomography (OCT) in cancer patients after drug-eluting stent (DES) placement. Background: Cancer treatment, owing to its cytotoxic and antiproliferative effects, could delay stent healing and increase stent thrombosis risk, especially when dual antiplatelet therapy (DAPT) is discontinued early for oncological treatment. OCT can assess stent endothelialization and other healing parameters, which may provide clinical guidance in these challenging scenarios. Methods: This single-center retrospective study enrolled all cancer patients who underwent OCT for assessment of vascular healing patterns after prior DES placement from November 2009 to November 2018. Primary study endpoints were stent healing parameters, including stent coverage, apposition, degree of expansion, neointimal hyperplasia heterogeneity, in-stent restenosis, stent thrombosis, and overall survival (OS). Results: A total of 67 patients were included in this study. Mean time between DES placement and OCT evaluation was 154 ± 82 days. Stent healing matched published values for DES in non-cancer patients (P ≥ 0.063). At 1 year, the OS was 86% (95% confidence interval [CI]: 78–96%) with 0% incidence of acute coronary syndrome. Advanced cancers and active chemotherapies were associated with inferior OS (P = 0.024, hazard ratio [HR]: 3.50, 95% CI: 1.18–10.42 and P = 0.026, HR: 2.65, 95% CI: 1.13–6.22, respectively), while stent healing parameters were unassociated with OS. Forty-one patients (61%) had DAPT duration ≤6 months. Conclusions: Stent healing of contemporary DES appears similar in cancer and non-cancer patients. Cardiovascular risk of cancer patients after DES placement can be managed to facilitate timely cancer therapies, as the underlying malignancy and active chemotherapy ultimately determine survival.